Contact tracing: Unearthing key epidemiological features of COVID-19. (June 2020) - Ish, Pranav; Agrawal, Sumita; Goel, Akhil Dhanesh; Gupta, Nitesh
COVID-19 is an emerging global pandemic with a steady rise in both morbidity and mortality over the past few months. Contact tracing of COVID-19 patients is an essential task to mitigate the spread. The following case was one of the initial patients reported from India and details the importance of contact tracing, timely testing and adequate quarantine/isolation in disease control.